ANALISIS MANAJEMEN RISIKO PT. AMANU ZAMZAM SAKINAH SOLO MENGHADAPI KEBIJAKAN PEMERINTAH DI MASA PANDEMI COVID-19 - Muhammad Permadi; M Muqoffa (Academica: Journal of Multidisciplinary Studies, 2020)
The Hajj and Umrah industry is one of the most growing and popular businesses in these years. Decree of the minister of religion of the Republic of Indonesia number 494 of 2020 concerning the cancellation of pilgrims during the Hajj pilgrimage in 2020 this decision is to prevent the spread of the Corona virus. The purpose of this study was to analyze and determine the risk management carried out by PT Amanu in the era of the Covid-19 pandemic. This study used a qualitative descriptive method, with primary and secondary data to study the situation and situation in the Covid-19 pandemic. Until now.This research is important to do to provide an overview to the public about the importance of risk management in the midst of a pandemic. The results of this research show that PT Amanu can survive the impact of the Haj and Umrah cancellation policy on the government by making various new breakthroughs and innovations.Keywords: government policy; covid 19 pandemic; risk management.